Comparison of mesoporous silicate supports for the immobilisation and activity of cytochrome c and lipase - Abdallah, Noreldeen Hassan.; Schlumpberger, Miriam.; Gaffney, Darragh; Hanrahan, John P.; Tobin, Joseph M.; Magner, Edmond (Journal of Molecular Catalysis B: Enzymatic, 2014)
peer-reviewed The activity and stability of Candida antartica lipase B (CALB) and cytochrome c immobilised on to, SBA-15 and a porous spherical silicate material (PPS), were examined. The materials possess similar pore diameters but have different morphologies, pore volumes and surface areas. CALB exhibited higher catalytic activity and stability on SBA-15 when compared to PPS, while cytochrome c showed similar catalytic activity on both materials. The activity of CALB immobilised on SBA-15 was retained (95%) after 7 uses, while CALB immobilised on PPS retained only 43% activity. Such changes can be mainly ascribed to the different physical properties (pore volume, surface area and pore shape) of the supports.